The Effect Of Credit Risk Management And Good Corporate Governance On The Financial Performance Of Conventional Banks With Operational Efficiency As An Intervening Variable (Case Study Of Conventional Banks Listed On The Indonesia Stock Exchange) - Febiansyah, Arfi; Hertina, Dede (UNIVED Press, 2026)
This study aims to analyze the effect of Credit Risk Management and Good Corporate Governance (GCG) on the Financial Performance of conventional banks with Operational Efficiency as a mediating variable. Secondary data were obtained from the financial reports of conventional banks listed on the Indonesia Stock Exchange for the period 2020–2024 and analyzed using panel data regression and mediation tests. The results show that Credit Risk Management has a positive effect on Operational Efficiency but a negative effect on Financial Performance. GCG has a positive effect on operational efficiency but no significant effect on Financial Performance. Operational Efficiency has a negative effect on Financial Performance but is able to mediate the relationship between Credit Risk Management and GCG on Financial Performance. These findings indicate that the implementation of effective Credit Risk Management and GCG can improve efficiency, although their impact on profitability is not yet consistent. This study provides implications for bank management to strengthen governance and risk control in order to promote sustainable financial performance.